HIPOKRISI PARLEMEN DALAM FORMULASI TINDAK PIDANA POLITIK UANG PADA PEMILIHAN KEPALA DAERAH - Fathurokhman, Ferry (Veritas et Justitia, 2022)
This research reveals a hypothesis that there is vested interest on regulating law in the house of representative regarding Law No. 1/2015 article 73 in term of money politics which is conducted by regional head candidate and analyze legal efforts that can be done to cope such issue. Although the law has been revised for three times, lastly by Law No.6/2020, yet regulation record that the house of representative persists ‘to protect’ its interest on regional head election is traceable. This research shows an understanding to society and stakeholders especially in the field of general election regarding lawmaking which deviates from penal policy theory. This research focuses on how legislation design on formulating Article 73 of Law No.1/2015 so it becomes non-exectubale norm? Theory of Postmodern Criminology is utilized to divulge political agenda of Article 73 of Law No.1/2015. This research is a research regarding a norm which relies heavily on secondary data. The result of the research proves that there is a consistent effort from the parliament  ‘to secure’ legislation process so article 73 cannot be implemented. Parliament intentionally and systematically has made article 73, particularly that related to money politic which may lead to disqualification, hard to be enforced.